Defining informality vs mitigating its negative effects - Elizabeth Ruppert Bulmer (IZA World of Labor, 2018)
There are more informal workers than formal workers across the globe, and yet there remains confusion as to what makes workers or firms informal and how to measure the extent of it. Informal work and informal economic activities imply large efficiency and welfare losses, in terms of low productivity, low earnings, sub-standard working conditions, and lack of social insurance coverage. Rather than quibbling over definitions and measures of informality, it is crucial for policymakers to address these correlates of informality in order to mitigate the negative efficiency and welfare effects.
Keywords: J08; J46; E26; J32; 330; definition of informality; informal employment; measurement; correlates of being informal